2007
DOI: 10.1021/ma0706935
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Toughening of Semicrystalline Polymers

Abstract: Dispersing particles within a semicrystalline polymer can result in remarkable impact strength improvement and opens promising routes toward super-tough materials. Although the technique is extensively employed to modify polymer properties, predicting which dispersions yield toughness remains a challenging issue. By comparing the characteristic lengths and deformation processes involved in toughening, we explain why a minimum matrix confinement or ligament thickness is required to induce ductility. Our model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 28 publications
4
66
2
Order By: Relevance
“…These corrections particularly concerned the cross-section effect which tends to overestimate the number of small particles and the projection effect due to the non-zero thickness of ultrathin sections. Details of this image analysis are given in a separate study [26].…”
Section: Characterizationmentioning
confidence: 99%
“…These corrections particularly concerned the cross-section effect which tends to overestimate the number of small particles and the projection effect due to the non-zero thickness of ultrathin sections. Details of this image analysis are given in a separate study [26].…”
Section: Characterizationmentioning
confidence: 99%
“…[1,2] Accordingly various toughening mechanism of nacre have been proposed, [3][4][5][6][7][8] and nacre has bioinspired a number of remarkable materials. [9][10][11][12][13] Here, in particular, we focus on a simple model of nacre [14] that provides simple understandings of the type recently revealed for spider webs, [15][16][17] (although it does not include recently found complex structures beyond the layered structure [18,19] ). This is because simple scaling laws were obtained for the model to predict the correct order of the fracture energy of nacre, on the basis of analytical solutions for two crack problems.…”
mentioning
confidence: 99%
“…particle size decreases exponentially and levels off at a given concentration. This behavior has been described extensively in the literature [49, 99,100] and can be explained by the change with time of the concentration of copolymer formed at the interface. To simulate the kinetics of this reaction, it is assumed that the concen tration, of the reactive groups at the interface is low, which means that the reactions at the interface end before the formation of a densely packed brush of copolymers.…”
Section: Role Of the Reaction Rate On The Dispersed Phase Morphologymentioning
confidence: 83%
“…The high BDTT is normally attributed to the existence of coarse ABS particles dispersed in the PBT matrix. Some authors have suggested that BDTT depends not only on particle size but also on interparticle distance, with a coarse morphology causing a larger interparticle distance [100][101][102][103][104][105][106][107]. Furthermore, there is evidence that the morphology of melt compounded PBT/ABS blends is unstable when they are injection molded [99].…”
Section: Polybutadiene Terephthalate Blendsmentioning
confidence: 99%